Strategi Peningkatan Pendapatan Masyarakat Pesisir dalam Memenuhi Kebutuhan Hidup - Caesa Rifandini Leksono Putri (Jurnal Al-Tatwir, 2021)
Work as a fisherman is dependent on marine resources. However, coastal communities still live in poverty and the increasingly sharp inequality is very prominent in fishing communities, where a group of people really enjoy the results of fish resources. This group is those who have modern fishing gear such as trawlers and the like that are supported by a mountain of protection and permits. On the other hand, most of them, namely traditional fishermen, still live in poverty. Efforts to build and improve the quality of life of all citizens of the nation, including fishermen, both socially, economically and are our common goals. This study will discuss how the strategy of increasing the income of coastal communities in meeting the needs of life. These strategies 1) Build and strengthen social institutions that are owned or existing in the community and develop the quality of human resources. 2) Assistance from the government for coastal communities Until now, the government has actually disbursed programs to overcome fishermen's poverty, such as aid package programs such as Small Investment Credit (KIK), Permanent Working Capital Credit (KMKP) and Bimas credit as mentioned above. . 3) Role of Extension Institutions Community empowerment efforts are expected to be able to play a role in improving the quality of human resources, especially in the form and change people's behavior to achieve a better standard of living. Poverty that occurs in traditional fishermen is caused by 3 (three) very influential factors, namely: 1) the quality of human resources 2) Economic factors; and 3) institutional factors. Poverty in coastal communities is natural and cultural poverty, consumptive lifestyles and the existence of the influence of prevailing customs and cultures. Lazy attitude is characterized by low utilization of free time when not going to sea. Fishermen prefer to use their free time with activities that are less economically productive.